Infestation of extraocular muscle by Cysticercus cellulosae. Issue 12 (December 1990) - DiLoreto, D A; Kennedy, R A; Neigel, J M; Rootman, J
Abstract : Reports of orbital cysticercosis are uncommon despite the high incidence of brain and ocular involvement. Infestation of extraocular muscle is exceedingly rare. Two cases of cysticercosis of the extraocular muscles are reported here. Surgical removal of the encysted parasites successfully resolved the infestation in both cases.